USING CARTOONS AND ANIMATED STORIES TO DEVELOP LISTENING AND COMPREHENSION SKILLS - Eshniyozova Jasmina Jo’rabekovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This work examines the role of cartoons and animated stories in developing listening and comprehension skills for language learners. By analyzing how these media integrate both visual and auditory elements, the study highlights their potential to engage learners through context-rich narratives, clear speech patterns, and frequent repetition of vocabulary. The use of animated content helps learners connect words with actions, emotions, and settings, providing a deeper understanding of language. Additionally, the study underscores the importance of engaging and interactive content, which not only aids comprehension but also motivates learners to stay actively involved in the language learning process. The paper further explores how cartoons of varying genres and complexity cater to different learner levels, offering a versatile tool for both children and adults. Ultimately, this research provides insights into how animated stories can serve as a fun and effective educational resource, enhancing the listening skills and overall language proficiency of learners. Abstract: This study explores the use of cartoons and animated stories as tools for enhancing listening and comprehension skills. These mediums are examined for their ability to provide contextual support through visual cues, engaging narratives, and natural speech patterns, all of which contribute to improved language acquisition. The study emphasizes the benefits of exposure to authentic conversational language, repeated vocabulary, and active listening strategies. Additionally, the use of cartoons in various genres and levels offers a flexible, enjoyable learning experience, making it an ideal method for both children and adults. The effectiveness of cartoons as a language learning tool is analyzed through examples of popular animated shows and their impact on comprehension, retention, and engagement.